Improving Students' Scientific Literacy by The Implementation of PBL Model Integrated with Climate Action - Cahyani, Sindy Regita; Lestari, Nurita Apridiana (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2024)
Improving Students' Scientific Literacy by The Implementation of PBL Model Integrated with Climate Action. This research aims to analyze the implementation, improvement, and response of students to the implementation of the integrated PBL model of climate action to increase students' scientific literacy at MA Matholi'ul Anwar. This type of research uses quantitative research with a true experiment control group pretest and posttest design. The subjects of this research were from X.1 is class control, X.2 is class experiment 1, and X.9 is class experiment 2. The research data was processed through calculations of learning implementation analysis, prerequisite tests, Wilcoxon test, N-gain analysis, Kruskal-Wallis test, effect size analysis, and student response questionnaire sheets. Based on the research results, it was concluded that (1) the implementation of the integrated PBL model for climate action to increase students' scientific literacy was carried out in the very good category, (2) there were significant differences in students' scientific literacy abilities before and after the implementation of the PBL mode. In class experiment 1 experienced a higher increase as shown by the results of the n-gain analysis with a score of 0.87, a score of 0.79 in experiment class 2, and a score of 0.76 in the control class, thus showing the implementation of the integrated PBL model of climate action effective to implement, (3) students' responses after implementing the integrated PBL climate action model obtained results in the very good category. The research implies that students show an attitude of caring about the environment, namely carrying out reforestation, 3R, and saving energy.